Analysing financial literacy and saving behaviour among university students - Mohd Rahim, Ariffin; Wan Amalina, Wan Abdullah@Wan Muda; Zunaidah, Sulong (2017)
Previous studies highlighted that financial literacy is still low and many people failed to manage their finances effectively. The objective of this paper is to determine the financial literacy level and students’ perception towards saving behaviour. Data were collected using self-administered questionnaire and there were 192 respondents from undergraduate students who enrolled for business administration degree programme at Universiti Putra Malaysia. The findings showed that saving behaviour, parental socialization and peer influence had positive correlation with financial literacy, whereas self-control showed negative correlation with financial literacy. The mean values for financial literacy among these respondents are still at moderate level. Each students needs to learn more knowledge in dealing with personal financial management and effective strategies to increase positive attitude towards saving behaviour. The higher education authority such as Ministry of Education can improve the existing business courses by adding personal financial management and encouraged more saving activities rather that spending too much money for unnecessary items. Parents always play the central role in facilitating and promoting their children’s saving or investment.